Characterization of Salmonella spp. isolated from patients below 3 years old with acute diarrhoea - Shobirin, M.H. Anis; Shuhaimi, M.; Abu‐Bakar, F.; Ali, A.M.; Ariff, A.; Nur‐Atiqah, N.A.; Yazid, A.M. (Springer, 2003)
Fifteen strains of Salmonella were isolated from children with clinically diagnosed diarrhoea aged below 3 years old, who had been admitted to K7 ward, Pediatric Institute, Kuala Lumpur Hospital. The isolates were tested for their susceptibility to a range of antimicrobial agents, and typed by serological tests and randomly amplified polymorphic DNA (RAPD) fingerprinting. All the strains had a similar pattern of antimicrobial susceptibility, where they were susceptible to a wide range of antimicrobial agents. The serological test has typed them into three serovars, which were identified as Salmonella enterica ser. Akanji, Salmonella enterica ser. Hindmarch and Salmonella enterica ser. Richmond. In contrast, the RAPD fingerprinting classed them into two major clusters, cluster 1 consisting of 12 strains of Salmonella and cluster 2 consisting of three strains of Salmonella.